2014
DOI: 10.1245/s10434-014-4266-5
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence in the Neck and Survival After Thyroidectomy for Metastatic Renal Cell Carcinoma

Abstract: Although significant improvement of local disease control in patients with thyroid metastases of RCC has been achieved during the last decade, overall outcome continues to be poor for patients with locally invasive thyroid metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
0
11
0
1
Order By: Relevance
“…Clinical presentation of ITM is nonspecific and tumors are often unsuspected especially when metastases develop many years after the primary diagnosis. Recently it has been reported that in 67% of ITM, indication to thyroidectomy was for suspected primary thyroid malignancies or nodular goiter [6]. Also in our case, ITM was the first metastatic site during follow-up for RCC removed 1 years before and it was misinterpreted as a primary thyroid tumor.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Clinical presentation of ITM is nonspecific and tumors are often unsuspected especially when metastases develop many years after the primary diagnosis. Recently it has been reported that in 67% of ITM, indication to thyroidectomy was for suspected primary thyroid malignancies or nodular goiter [6]. Also in our case, ITM was the first metastatic site during follow-up for RCC removed 1 years before and it was misinterpreted as a primary thyroid tumor.…”
Section: Discussionmentioning
confidence: 58%
“…This event develop more often in patients with tumor spread to adjacent structures, and thyroid metastases exceeding 3.5 cm [6]. The risk of cervical recurrence was not reduced by total vs subtotal thyroidectomies [6].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…RCC metastases to the thyroid usually appear as metachronous lesions, often presenting several years after nephrectomy. Moreover, their association with other MGM sites, mainly the pancreas, has been retrospectively documented [13,14] . Parotid metastases of RCC are rare, with a review in 2008 identifying only 26 cases of RCC metastasizing to the parotid [15] .…”
Section: Discussionmentioning
confidence: 99%